2012
DOI: 10.4103/1658-354x.97027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of addition of ketamine, fentanyl and saline with Propofol induction on hemodynamics and laryngeal mask airway insertion conditions in oral clonidine premedicated children

Abstract: Background:The aim of this double-blind, prospective, randomized, controlled study was to compare the effect of addition of ketamine; fentanyl and saline with propofol anesthesia on hemodynamic profile and laryngeal mask airway (LMA) insertion conditions in oral clonidine premedicated children.Methods:180 children (age 2 - 10 years) were at first given oral clonidine (4 μg/kg) 90 minutes before operation, and then were randomly allocated to receive either ketamine 0.5 mg/kg (n=60), fentanyl 1 μg/kg (n=60) or 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 12 publications
11
7
0
Order By: Relevance
“…Similar to our findings, HR decreased significantly at all times when compared to preinduction values in the propofol group. Similar findings were reported by other researches [6,27]. The incidence of injection pain in the present study was significantly lower in PK and PM groups than in propofol group.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our findings, HR decreased significantly at all times when compared to preinduction values in the propofol group. Similar findings were reported by other researches [6,27]. The incidence of injection pain in the present study was significantly lower in PK and PM groups than in propofol group.…”
Section: Discussionsupporting
confidence: 93%
“…Every patient had their laryngeal mask airway successfully inserted on the first attempt. Our data compare favorably to other studies where ease of laryngeal mask airway placement and airway complications were recorded when the laryngeal mask airway was placed after the IV . In these studies, placement of the laryngeal mask airway Unique or Classic resulted in easy insertion rates of 87.5–98% (98.4% in our study), laryngospasm in 0–5% (0% in our study) and coughing in 0–14% (0% in our study).…”
Section: Discussionsupporting
confidence: 84%
“…A study by Furuya et al showed that administration of ketamine before induction with propofol preserved hemodynamic stability compared with induction with propofol alone ( 20 ). Another study by Ghatak et al showed that addition of ketamine with propofol provides hemodynamic stability in children premedicated using clonidine for insertion of laryngeal mask airway (LMA) ( 21 ). However, Ozgul et al showed that ketamine-propofol combination provided minimal hemodynamic changes during insertion of laryngeal tube-suction ( 22 ).…”
Section: Discussionmentioning
confidence: 99%